Essays on Geography and GIS, Vol. 4 - Nedjeljko Frančula (Kartografija i Geoinformacije, 2012)
The fourth volume of ESRI's free e-books titled Essays on Geography and GIS was published in May 2012. It consists of 18 short papers in 74 pages and is available free of charge at: http://www.esri.com/library/bestpractices/essays-ongeography-gis-vol4.pdf.